Proteomics Landscape of Host-Pathogen Interaction in Acinetobacter baumannii Infected Mouse Lung - Li, Xin; Liu, Xiaofen; Horvatovich, Peter; Hu, Yingwei; Zhang, Jing (Frontiers in Genetics, 2021)
Acinetobacter baumannii is an important pathogen of nosocomial infection worldwide, which can primarily cause pneumonia, bloodstream infection, and urinary tract infection. The increasing drug resistance rate of A. baumannii and the slow development of new antibacterial drugs brought great challenges for clinical treatment. Host immunity is crucial to the defense of A. baumannii infection, and understanding the mechanisms of immune response can facilitate the development of new therapeutic strategies. To characterize the system-level changes of host proteome in immune response, we used tandem mass tag (TMT) labeling quantitative proteomics to compare the proteome changes of lungs from A. baumannii infected mice with control mice six hours after infection. A total of 6218 proteins were identified in which 6172 could be quantified. With threshold p < 0.05 and relative expression fold change > 1.2 or < -1.2, we found 120 differentially expressed proteins. Bioinformatics analysis showed that differentially expressed proteins after infection were associated with receptor recognition, NADPH oxidase (NOX) activation and antimicrobial peptides. These differentially expressed proteins were involved in the pathways including leukocyte transendothelial migration, phagocyte, neutrophil degranulation, and antimicrobial peptides. In conclusion, our study showed proteome changes in mouse lung tissue due to A. baumannii infection and suggested the important roles of NOX, neutrophils, and antimicrobial peptides in host response. Our results provide a potential list of proteins candidates for the further study of host-bacteria interaction in A. baumannii infection. Data are available via ProteomeXchange with identifier PXD020640.